2020
DOI: 10.1038/s41598-020-71372-5
|View full text |Cite
|
Sign up to set email alerts
|

A 2,000-year Bayesian NAO reconstruction from the Iberian Peninsula

Abstract: The North Atlantic Oscillation (NAO) is the major atmospheric mode that controls winter European climate variability because its strength and phase determine regional temperature, precipitation and storm tracks. The NAO spatial structure and associated climatic impacts over Europe are not stationary making it crucial to understanding its past evolution in order to improve the predictability of future scenarios. In this regard, there has been a dramatic increase in the number of studies aimed at reconstructing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 79 publications
2
19
0
Order By: Relevance
“…In a multi-centennial perspective (1680-2019 CE), Diodato et al (2020a) showed that substantially neutral (winter) NAO states (without a clear dominance of positive or negative phases) correspond to a decline of erosivity extremes throughout the Mediterranean. In the present basin-wide study, we observed (Figure 7E) a predominantly weak anticorrelation between the reconstructed erosivity time-series and the proxy-based multi-annual NAO reconstruction of Hernández et al (2020). These studies highlight the need for a more detailed understanding of the linkages between largescale atmospheric and oceanic oscillations and different erosivity outputs (e.g., average or extreme events), which depend on the geographic context (e.g., large regions or small river basins) and the temporal frame (e.g., seasonal or yearly) in which the hydrological response is assessed.…”
Section: Influence Of Solar and Teleconnection Cyclessupporting
confidence: 57%
See 1 more Smart Citation
“…In a multi-centennial perspective (1680-2019 CE), Diodato et al (2020a) showed that substantially neutral (winter) NAO states (without a clear dominance of positive or negative phases) correspond to a decline of erosivity extremes throughout the Mediterranean. In the present basin-wide study, we observed (Figure 7E) a predominantly weak anticorrelation between the reconstructed erosivity time-series and the proxy-based multi-annual NAO reconstruction of Hernández et al (2020). These studies highlight the need for a more detailed understanding of the linkages between largescale atmospheric and oceanic oscillations and different erosivity outputs (e.g., average or extreme events), which depend on the geographic context (e.g., large regions or small river basins) and the temporal frame (e.g., seasonal or yearly) in which the hydrological response is assessed.…”
Section: Influence Of Solar and Teleconnection Cyclessupporting
confidence: 57%
“…(A) Evolution (red arrow indicating the change-point year 1490) of estimated annual rainfall erosivity (blue circles; out-of-scale value in the year 1688) with the relative 95th and 98th percentiles (horizontal bold yellow and pink lines, respectively), and the 11-years Gaussian filtered erosivity series (bold blue curve), (B) decadal-scale variability of the 98th percentile of rainfall erosivity (black curve), (C) wavelet spectrum of the rainfall erosivity time series with bounded colors identifying 0.05 significance areas (the bell-shaped, black contour marks the limit between the reliable region and the region below the contour where the edge effects occur, a.k.a. cone of influence), (D) Atlantic Multidecadal Variability (AMV;Wang et al, 2017), (E) North Atlantic Oscillation (NAO;Hernández et al, 2020). The bottom colored band indicates mean Italian summer (June-July-August) temperature anomalies (°C) with respect to the 1961-1990 climatology(Luterbacher et al, 2016) for the Medieval Climate Anomaly, three phases of the Little Ice Age (with in dark blue the years of the Maunder minimum) and the Modern Warming Period.…”
mentioning
confidence: 99%
“…Interesting results are also obtained by linear methods on certain dominant factors, such as NAO, which determine the large-scale atmospheric variability in Europe 77 . But this happens when there are no large deviations from linearity in the connection of phenomena.…”
Section: Resultsmentioning
confidence: 99%
“…( a ) Wavelet spectrum of the rainfall erosivity time-series with bounded colours identifying 0.05 significance areas (the bell-shaped, black contour marks the limit between the reliable region and the region below the contour where the edge effects occur, a.k.a. cone of influence ( b ) North Atlantic Oscillation (annual NAO from Hernández et al 100 ); ( c) Trend of quantile-rainfall erosivity with return period T = 50 years (red curve); ( d) Evolution (red arrow indicating the change-point year 1495) of estimated annual rainfall erosivity (blue circles) with the relative smoothed trend by the 11-year Gaussian function (bold blue curve). The y -right axes in ( c ) is in the reverse-scale.…”
Section: Resultsmentioning
confidence: 99%